Some neck swellings are serious; a case of Lemierre's Syndrome - Ali Raza Ghani; Mohsin Hamid; Ahsan Raza; Rizwan Naseer; Joseph Crocetti (Greater Baltimore Medical Center, 2017)
Lemierre's syndrome also termed post-anginal septicemia, is a disease characterized by internal jugular septic thrombophlebitis leading to Fusobacterium septicemia with multiple metastatic foci following an oropharyngeal infection. Diagnosis and management is challenging and can result in fatal consequences due to potential multisystem involvement and multiple complications. We describe here a case of Lemierre's syndrome with multifocal pneumonia, acute renal failure and protracted course of illness over forty days with successful recovery. A brief overview of literature is also presented.